2001
DOI: 10.1086/323969
|View full text |Cite
|
Sign up to set email alerts
|

A Robotic Wide‐Angle Hα Survey of the Southern Sky

Abstract: We have completed a robotic wide-angle imaging survey of the southern sky (δ = +15 • to −90 • ) at 656.3 nm wavelength, the Hα emission line of hydrogen. Each image of the resulting Southern H-Alpha Sky Survey Atlas (SHASSA) covers an area of the sky 13 • square at an angular resolution of approximately 0.8 arcminute, and reaches a sensitivity level of 2 rayleigh (1.2 × 10 −17 erg cm −2 s −1 arcsec −2 ) per pixel, corresponding to an emission measure of 4 cm −6 pc, and to a brightness temperature for microwave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
469
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(483 citation statements)
references
References 35 publications
14
469
0
Order By: Relevance
“…It is almost certainly responsible for the anomalously high DM of PSR J0537−69 ( Table 13). As seen in radio continuum (Hughes et al 2007) and Hα (Gaustad et al 2001), 30 Doradus is not far from the nominal center of the LMC at (a 30D , ) d 30D =(05 h 40 m , - 69 ¢ 00 ) and it is believed to be at a similar distance. We model its electron density as a spherical Gaussian distribution:…”
Section: The Magellanic Cloudsmentioning
confidence: 91%
“…It is almost certainly responsible for the anomalously high DM of PSR J0537−69 ( Table 13). As seen in radio continuum (Hughes et al 2007) and Hα (Gaustad et al 2001), 30 Doradus is not far from the nominal center of the LMC at (a 30D , ) d 30D =(05 h 40 m , - 69 ¢ 00 ) and it is believed to be at a similar distance. We model its electron density as a spherical Gaussian distribution:…”
Section: The Magellanic Cloudsmentioning
confidence: 91%
“…We also examined the spectral energy distributions (SEDs) and the correlation between measured radio fluxes and Balmer line fluxes estimated from the SuperCOSMOS H-alpha Survey (SHS; Gaustad et al 2001) Hα images (the MASH part of the sample) or found in the literature (the previously known fraction of the sample). We also present derived distances, radii and physical properties of the detected objects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, VB could only use the Hipparcos input catalogue (HIC) to determine the proper-motion direction of the central star. As the Hipparcos catalogue is now completed, its astrometrical data together with the almost complete Hα allsky surveys Virginia Tech Spectral Survey 1 (VTSS; Dennison et al 1997) and Southern Hemispheric Hα Sky Survey Atlas 1 (SHASSA; Gaustad et al 2001), the VB sample is reanalysed here, now using the Hα emission line.…”
Section: Introductionmentioning
confidence: 99%